Development of Prototype a Nutrient Automation System for Hydroponic System - Jumaat, Siti Amely; Emir Azmi, Muhammad Musairi (Evolution in Electrical and Electronic Engineering, 2021)
Nutrients are essential for their use in the process of plant growth. However, the usage of the concentration of the nutrients must be controlled because it can damage the plant. In order to do so, the quantity of nutrients is evaluated before it is fed to the plant. Automatic mixer can save so much energy in mixing the nutrients. Human energy are no longer needed in mixing the nutrients. Overall, this project discussed about the development of prototype a nutrient automated system for hydroponic which was accessed by the sensor to detect the overuse of the nutrients. The major parts of this project consists of mixer and electrical conductivity (EC) sensor. The nutrients solution are the combination of water and AB nutrients. The mixer was controlled by the DS3231 Real Time Clock (RTC) module where the motor of the mixer is triggered by single channel relay at the desired time to operate. The DS3231 RTC module will keep the accurate date for the system. The amount of nutrients usage was monitored in the serial monitor of Arduino IDE software. The data for the timer settings was kept inside the Arduino IDE software which the system will operated at desired time as long as the mixer is supplied by power.